Artificial intelligence and big data : the birth of a new intelligence - Iafrate, Fernando (ISTE, Ltd. ; Wiley, 2018)
With the idea of "deep learning" having now become the key to this new generation of solutions, major technological players in the business intelligence sector have taken an interest in the application of Big Data. In this book, the author explores the recent technological advances associated with digitized data flows, which have recently opened up new horizons for AI. The reader will gain insight into some of the areas of application of Big Data in AI, including robotics, home automation, health, security, image recognition and natural language processing.- Resumé vydavatel
Keywords: big data; umělá inteligence; artificial intelligence; monografie; elektronické knihy; monographs; electronic books